The complete guide to Asperger's syndrome - Attwood, Tony. 4 0 16; 5 (London : Jessica Kingsley Publisher, 2008)
A comprehensive guide to Asperger's syndrome that provides information on every aspect of the syndrome, including its symptoms, diagnosis, treatment, causes, impact on a child's emotional and social development, and other related topics.
What is Asperger's syndrome? -- The diagnosis -- Social understanding and friendship -- Teasing and bullying -- Theory of mind -- The understanding and expression of emotions -- Special interests -- Language -- Cognitive abilities -- Movement and coordination -- Sensory sensitivity -- Life after school: college and career -- Long-term relationships -- Psychotherapy -- Frequently asked questions.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Asperger's syndrome. -- 20; 20; 2